The Effect of Removing Early Retirement on Mortality - Cristina Bellés Obrero; Sergi Jiménez-Martín; Han Ye (Institute of Labor Economics (IZA), 2022)
This paper sheds new light on the mortality effect of delaying retirement by investigating the impacts of the 1967 Spanish pension reform. This reform exogenously changed the early retirement age, depending on the date individuals started contributing to the Social Security system. Those contributing before 1 January 1967 maintained the right to voluntarily retire early (at age 60), while individuals who started contributing after that date could not voluntarily claim a pension until the age of 65. Using the Spanish administrative Social Security data, we find that the reform delayed the individuals' labour market exit by around half a year and increased the probability that individuals take up disability pensions, partial pensions, and no pensions. We show evidence that delaying exiting employment increases the hazard of dying between the ages of 60 and 69, for almost all individuals. Heterogeneous analysis indicates that the increase in mortality is stronger for those employed in low-skilled, physically and psychosocially demanding jobs. Moreover, we show that allowing for flexible retirement schemes, such as partial retirement, mitigates the detrimental effect of delaying retirement on mortality.
Keywords: I10; I12; J14; J26; 330; delaying retirement; mortality; heterogeneity; flexible retirement